2019
DOI: 10.1038/s41598-019-39493-8
|View full text |Cite
|
Sign up to set email alerts
|

Low oxygen post conditioning prevents thalamic secondary neuronal loss caused by excitotoxicity after cortical stroke

Abstract: In the current study, we were interested in investigating whether Low oxygen post-conditioning (LOPC) was capable of limiting the severity of stroke-induced secondary neurodegeneration (SND). To investigate the effect of LOPC we exposed adult male C57/BL6 mice to photothrombotic occlusion (PTO) of the motor and somatosensory cortex. This is known to induce progressive neurodegeneration in the thalamus within two weeks of infarction. Two days after PTO induction mice were randomly assigned to one of four groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 47 publications
(46 reference statements)
1
30
0
1
Order By: Relevance
“…In the same study, similar observations is observed after an intracortical injection of kainic acid, suggesting that excitotoxicity can lead to secondary thalamic injury (17). Another study further emphasizes the importance of excitotoxicity in secondary thalamic injury, by demonstrating that interruption of the interactions between NMDAR and PSD95 after low oxygen post-conditioning treatment can reduce secondary thalamic injury (23). Although these studies suggest that excitotoxicity is associated with the secondary thalamic injury, the underlying mechanisms of glutamate-mediated secondary thalamic injury remain to be further elucidated.…”
Section: Excitotoxicitysupporting
confidence: 55%
See 1 more Smart Citation
“…In the same study, similar observations is observed after an intracortical injection of kainic acid, suggesting that excitotoxicity can lead to secondary thalamic injury (17). Another study further emphasizes the importance of excitotoxicity in secondary thalamic injury, by demonstrating that interruption of the interactions between NMDAR and PSD95 after low oxygen post-conditioning treatment can reduce secondary thalamic injury (23). Although these studies suggest that excitotoxicity is associated with the secondary thalamic injury, the underlying mechanisms of glutamate-mediated secondary thalamic injury remain to be further elucidated.…”
Section: Excitotoxicitysupporting
confidence: 55%
“…When a primary ischemic injury is generated in S1, we observe a secondary thalamic injury in VPM and PoM at Day 30 after stroke (9). In other studies, a primary injury in the motor cortex can lead to a secondary thalamic injury in thalamic posterior area and ventral posterolateral nuclei (VPL) area (7,23). In a bilateral endothelin-1-induced infarct in the pre-frontal cortex, secondary degeneration is observed in dorsomedial nucleus of the thalamus and retrosplenial cortex (24).…”
Section: Methods and Strategies To Identify Secondary Thalamic Injurymentioning
confidence: 64%
“…Photothrombotic occlusion was performed as described previously [91][92][93]. Firstly, mice were anesthetized with 2% isoflurane and placed on a temperature-controlled (37 • C ± 1) stereotaxic frame.…”
Section: Photothrombotic Occlusionmentioning
confidence: 99%
“…The general measures of reduced apoptosis are taken as a reduction in caspase activation and a higher ratio of Bcl-2 to Bax (Chen et al, 2020;Jia et al, 2020). Combatting excitotoxicity often ultimately focuses either on reducing glutamate signaling, mostly through NMDA receptors, or reducing intracellular calcium accumulation and waves in connected cells (Maiolino et al, 2019;Pietrogrande et al, 2019). The improvement of metabolism is closely tied to glucose uptake to sustain cells in the absence of production (Ren et al, 2008).…”
Section: Cell Survivalmentioning
confidence: 99%